Chronic thromboembolic pulmonary hypertension in young woman with history of caesarian section (Faculty of Medicine Universitas Indonesia, 2014)
Chronic thromboembolic pulmonary hypertension (CTEPH) is one of subgroups of pulmonary hypertension. This is a serious medical condition that severely under diagnosed. CTEPH is commonly underdiagnosed due to non specific symptoms and lack of diagnostic tools. The aim of this presentation is to discuss the etiology, risk factors, diagnosis and management of CTEPH. A 36-year-old woman presented with easily fatigue and dyspneu on effort since two years ago. The symptom occured about three months after she gave birth with caesarian section due to preeclampsia. Further history taking, physical examination, electrocardiography (ECG) and echocardiography were highly suggestive of pulmonary hypertension. No deep vein thrombosis (DVT) was found on vascular femoral sonography. It was found after the lung perfusion scintigraphy performed that she actually had CTEPH. This patient was categorized as inoperable because CT pulmonary angiography showed no thrombus. The patient got pulmonary vasodilator and oral anticoagulant for lifelong.